2008
DOI: 10.1007/s00213-008-1438-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of galanin on cocaine-mediated conditioned place preference and ERK signaling in mice

Abstract: Rationale-The neuropeptide galanin and its receptors are expressed in brain regions implicated in the rewarding effects of natural stimuli and drugs of abuse. Galanin has been shown to attenuate neurochemical, physiological and behavioral signs of opiate and amphetamine reinforcement.Objective-In the current study, we present evidence that galanin modulates neurochemical and behavioral correlates of response to exposure to cocaine.Methods-Mice lacking the neuropeptide galanin (Gal −/−) and wild type (Gal +/+) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 54 publications
(93 reference statements)
1
31
1
Order By: Relevance
“…These data are consistent with previous reports implicating a protective role for galanin receptors in morphine and cocaine reward (Zachariou et al, 1999;Narasimhaiah et al, 2009). Galanin is reported to have an inhibitory effect on dopamine release in rat striatal slices (Tsuda et al, 1998), a finding that supports the ability of galnon to attenuate rewarding effects of drugs of abuse.…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…These data are consistent with previous reports implicating a protective role for galanin receptors in morphine and cocaine reward (Zachariou et al, 1999;Narasimhaiah et al, 2009). Galanin is reported to have an inhibitory effect on dopamine release in rat striatal slices (Tsuda et al, 1998), a finding that supports the ability of galnon to attenuate rewarding effects of drugs of abuse.…”
Section: Figuresupporting
confidence: 91%
“…In addition, mice overexpressing the galanin peptide in noradrenergic neurons show decreased morphine withdrawal signs, while galanin knockout (Gal À/À ) mice show increased withdrawal signs (Zachariou et al, 2003). Gal À/À mice also show greater preference for cocaine, an effect reversed by galnon administration (Narasimhaiah et al, 2009). Furthermore, transgenic mice that overexpress galanin in the brain are less sensitive to amphetamine-induced increases in locomotor activity (Kuteeva et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…This suggests that DA output in the nucleus accumbens, regulated by NMDA receptors in the IL, function on D1/D2 receptors to control behavioral output. A number of reports have shown that DA-stimulating drugs elevate pERK in the nucleus accumbens (Janes et al 2009;Kim and Kim 2008;Narasimhaiah et al 2009;Schumann and Yaka 2009;Sun et al 2008), suggesting that DA, working via D1/D2 receptors, phosphorylates ERK. One possible regulatory mechanism of DA output by the IL is via AMPA receptors at the level of the VTA (Brog et al 1993;Mathe et al 1998;Sesack et al 1989).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, peptides that regulate feeding as well as responses to drugs of abuse could have extremely complex effects on alcohol intake. Both pharmacological and genetic studies have shown that galanin normally decreases opiate and cocaine reward [1, 11,67]. In contrast, galanin increases intake of ethanol [68 -70], increases hypothalamic expression of the mRNA encoding galanin [71,72] and potentially decreases GalR1 [73].…”
Section: Galanin and Alcoholmentioning
confidence: 99%